PENGARUH PERSEPSI KEMUDAHAN, KEBERMANFAATAN DAN KEPUASAN PENGGUNAAN E-FILING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi pada KPP Pratama Candisari Semarang) - Deviana Wahyu Purwiyanti; Herry Laksito (Diponegoro Journal of Accounting, 2020)
The purpose of this study is to examine the impact of perceived ease, usefulness, and satisfaction of e-filing on the compliance of individual taxpayers who are registered at Pratama Candisari Semarang Tax Office. The dependent variable used in this study is personal taxpayers compliance. While the perception of convenience, usefulness, and satisfaction of the use of e-filing is used as an independent variable in this study. The sample in this study consisted of 100 individual taxpayers who were registered at Pratama Candisari Semarang Tax Office. The data used in this study are primary data and sampling using purposive sampling method. The analysis technique used in this study to test the hypothesis is multiple linear regression analysis. Based on the test result in this study indicate that the perception of ease of use of e-filing has a significant positive effect on the compliance of individual taxpayers who are registered at Pratama Candisari Semarang Tax Office. In addition, the perceived usefulness of the use of e-filing also has a significant positive effect on the compliance of individual taxpayers who are registered at Pratama Candisari Semarang Tax Office. The third independent variable is satisfaction of using e-filing also has a significant positive effect of the compliance of individual taxpayers who are registered at Pratama Candisari Semarang Tax Office.